Genome-wide landscape of miRNA-mRNA-lncRNA-circRNA ceRNA network in Nanos2 deficient mice - Hongyi Li; Yuan Li; Yuting Wang; Lijian Liu; Ji Cui; Mao Zhang; Yiming Yan (PLoS ONE, 2025)
Nanos2 plays a key role in self-renewing spermatogenic stem cells (SSCs) and maintains the stem cell state during spermatogenesis. Alleles of the Nanos2 gene knockout showed germline ablated but otherwise structurally normal. To identify the probable ceRNA regulator involved in the process of spermatogenesis by Nanos2, whole transcriptome sequencing was performed in the testes between Nanos2 knock out mice and wild type mice. Finally, a total of 8644 Differentially expressed (DE) mRNAs,180 DE miRNAs, 9538 DE lncRNA and 481 DE circRNAs were identified. Three of each RNAs were selected randomly and identified by real-time PCR to verify the accuracy of sequencing. GO and KEGG functional enrichment analyses revealed similar result of DE mRNAs and target of DE miRNAs/lncRNAs/ circRNAs, mainly involved in the generation, composition, and activity of sperm cells. Furthermore, the regulatory ceRNA network of miRNA(up)-circRNA-lncRNA-mRNA and miRNA(down)-circRNA-lncRNA-mRNA were constructed based on the common targeted miRNA.The results enable us to better understand the interaction of coding RNA and non coding RNA in regulating the generation of spermatogenic stem cells through Nanos2 pathway, and also provided novel insights into molecular mechanism of spermatogenesis.